Polyparadigmatic uncertainty of international economic relations in the global security system - Sokhatskyi, Oleksandr (Herald of Economics, 2024)
Introduction. The dominant paradigms of international economic relations remain the market economy, the liberalization of world trade, globalization and the integration of national markets into world markets and their openness, which were supposed to contribute to economic development, increased well-being and sustainable peace on the planet. However, the realities turned out to be the opposite, the economies of the countries of the world are developing unevenly, the gap between rich and poor countries is growing, poverty gives rise to terrorism, and political conflicts began to be resolved by military means. Goal. The purpose of the article is to justify the state of polyparadigmatic uncertainty in the implementation of international economic relations for the restoration of the global security system in the conditions of global instability, as well as the need for a new reading of known theories and their addition with alternative ideas. Methods. In accordance with the outlined goal, the article uses general scientific methods of research, in particular, the historical method for analyzing the state of global security for the period from 1946 to 2023 through the prism of the emergence of paradigms of international economic relations. In the process of research, the methodological approach of Thomas Kuhn regarding scientific paradigms, the sequence of creation of new knowledge, starting from the period of initial pre-paradigmality, when there was no single accepted model for the study of scientific problems, to the creation of dominant paradigms, within which the main scientific explorations are carried out in specific time frames, was used. Results. Six periods of emergence, formation and paradigm changes of international economic relations in the system of global security are distinguished, from the period of initial pre-paradigmaticity to the current state of polyparadigmatic uncertainty. Prospects. The complexity of the problems raised requires further research into the impact of alternative international economic paradigms on the global security system. In particular, empirical verification of the consequences of their use. Discussions may take place regarding possible new readings of known dominant doctrines or syntheses of them with alternative doctrines.